Performance evaluation of optimization models in the determination of wastewater treatment efficiencies inside watersheds - Santoro,Mariana Coelho (2016)
ABSTRACT Determination of sewage treatment plants pollutant removal efficiencies, considering the protection of water resources, is very difficult because it involves complex analysis that must take into account multiple discharges into watercourses presenting different self depuration capacities. The research aimed to evaluate different optimization models for determination of minimum sewage treatment efficiencies for plants located in a watershed. The analyzed optimization models involves minimization of the sum of treatment efficiencies and minimization of inequity between sewage treatment efforts. Water quality mathematical model and Genetic Algorithm were combined in a MatLab software computing environment. The Pardo river watershed is the study area. Pardo river is a tributary of the Itapemirim river, important watercourse located in the southern part of Espirito Santo State, in Brazil. The results indicate that the optimization models that incorporate measurement of equity as a problem restriction did not generate consistent answers, probably because of the wide range of sewage loads values considered in the Pardo river watershed. The models that incorporate equity measures in the objective function showed satisfactory performance and resulted in very close values for minimum sewage treatment efficiencies.